Двухрежимный источник колебаний О-типа субтерагерцового диапазона. - Одаренко, Е. Н.; Шматько, А. А.; Юдинцев, П. В. (Weber Co., 2009)
The nonlinear multidimensional theory of the subterahertz O-type dual-mode source on the basis of the dis- tributed self-reactance modulation of electron beam by BWO oscillations and amplification of diffraction radiation on the harmonics of BWO frequency is developed. Numerical investigations of output characteristics of BWO oscillator and parametric amplifier of diffraction radiation are performed.
Keywords: субтерагерцовый диапазон; двухрежимный прибор О-типа; режим ЛОВ; режим ГДИ